Application of an Integrated Model of Management and Design of Balanced Scorecard in the Organization - Janík, Aleš; Vysoká škola ekonomická v Praze. Fakulta managementu; Pirožek, Petr, 1971-; Tripes, Stanislav (2013)
The Master's thesis "Application of an Integrated Model of Management and Design of Balanced Scorecard in the Organization" focusing on the definition of internal management analysis with target to evaluate the economic success of the company TOPAZ s.r.o. with using of Balanced Scorecard method. The analyzed entity operates in the glass industry and is engaged in the production of luxury domestic glass. Thesis is devided on three parts. First theoretical part defines the current company problems and the potentials for the solving of. The second part - practical, uses an genuine integrated model of management together with Balanced Scorecard method as a tool for definition, continous measurement and performance monitoring of company growth. The results and outputs from should brings the real feed-back to the company with target to prepare strategic map and benchmark for the right strategic company objectives and goals definition. As a key point for performance measurement system was set up Economic Value Added (EVA) indicator. Third part includes conclusion and complete evaluation of the thesis from the view of value added positives reached on
Vedoucí práce: Petr Pirožek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2013
Obsahuje bibliografii
Rok obhajoby 2013
Keywords: strategický management; Balanced Scorecard; ekonomická přidaná hodnota; management [obor dipl. práce]; diplomové práce; strategic planning; Balanced Scorecard; economic value added; master's theses